Breeding for the Main Agricultural Farming of Arabica Coffee - Bertrand, Benoît; Villegas Hincapié, Andres Mauricio; Marie, Lison; Breitler, Jean-Christophe (Frontiers in Sustainable Food Systems, 2021)
The main Arabica coffee breeding programmes in Latin America have so far focused on the selection of varieties adapted to intensive full-sun farming systems. Meanwhile, little attention has been paid to breeding varieties specifically adapted to shade which is the main characteristic of agroforestry systems (AFS). Yet the Specialty Coffee sector is currently expanding and seeking specific sensory qualities related to exotic varieties. There is no breeding program to create new varieties for this type of market. For the first time we report an experiment for comparing the selection at full-sun compared to a selection under shade. F1 hybrids and their parents (pure lines and Ethiopian accessions) were studied in a factorial-crossing plan. Two trials were set up: one in full sun and the other under shade. We measured the tree volume, the yield (3 years), the bean size, the bean NIRS signature and the final cupping score. Beans size and final cupping score seemed relatively unaffected by shading and we observed a strong maternal heritability for bean size. In both trial, the F1 hybrids produced 75-80% more than the maternal lines and 40-50% more than the male parents in the shade and sun trial, respectively. By opting for F1 hybrid, it is possible to increase productivity under both shade and full-sun while at the same time achieving good sensory qualities. Selecting a F1 hybrid with ‘Specialty coffee’ seems exceptional. This raises a fundamental issue concerning the maternal heritability of seed biochemical composition. We conclude that selection under shade is essential for the selection of varieties adapted to AFS.